Population based study on patients with traumatic brain injury suggests increased risk of dementia. Issue 11 (27th July 2012) - Wang, Hao-Kuang; Lin, Sheng-Hsiang; Sung, Pi-Shan; Wu, Ming-Hsiu; Hung, Kuo-Wei; Wang, Liang-Chao; Huang, Chih-Yuan; Lu, Kang; Chen, Han-Jung; Tsai, Kuen-Jer
Abstract : Objective: The relationship between traumatic brain injury (TBI) and the risk of dementia remains controversial. This population based study was designed to estimate and compare the risk of dementia in TBI and non-TBI individuals during the 5 year period after TBI. Methods: This study was a retrospective cohort study. Data were obtained from the Longitudinal Health Insurance Database 2000. We included 44 925 patients receiving ambulatory or hospital care and 224 625 non-TBI patients; patients were matched for sex, age and year of index use of healthcare. Patients <15 years of age and those admitted to the intensive care unit were excluded. Each individual was studied for 5 years to identify the subsequent development of dementia. Data were analysed by Cox proportional hazard regression. Results: During the 5 year follow-up period, 1196 TBI (2.66%) and 224 625 non-TBI patients (1.53%) patients developed dementia. During the 5 year follow-up period, TBI was independently associated with a 1.68 (range 1.57–1.80) times greater risk of dementia after adjusting for sociodemographic characteristics and selected comorbidities. Conclusions: The findings of this study suggest an increased risk of dementia among individuals with TBI. We suggest the need for more intensive medical monitoring and health education in individuals with TBI.